A Systematic Review on Secondary Metabolites of Paecilomyces Species: Chemical Diversity and Biological Activity - Li, Xiu-Qi; Xu, Kuo; Liu, Xin-Min; Zhang, Peng (Planta Medica, 2020)
Fungi are well known for their ability to synthesize secondary metabolites, which have proven to be a rich resource for exploring lead compounds with medicinal and/or agricultural importance. The genera Aspergillus, Penicillium, and Talaromyces are the most widely studied fungal groups, from which a plethora of bioactive metabolites have been characterized. However, relatively little attention has been paid to the genus Paecilomyces, which has been reported to possess great potential for its application as a biocontrol agent. Meanwhile, a wide structural array of metabolites with attractive bioactivities has been reported from this genus. This review attempts to provide a comprehensive overview of Paecilomyces species, with emphasis on the chemical diversity and relevant biological activities of these metabolic products. Herein, a total of 148 compounds and 80 references are cited in this review, which is expected to be beneficial for the development of medicines and agrochemicals in the near future.
Keywords: Paecilomyces; secondary metabolites; chemical diversity; biological activity